Centella asiatica in food and beverage applications and its potential antioxidant and neuroprotective effect - Hashim, Puziah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Centella asiatica L. is traditionally used as a medicinal herbs and alternative medicine in treating numerous kinds of diseases. The use of Centella in food and beverages has increased over the years. Its potential antioxidant and neuroprotective activity has been widely claimed in many reports and basically is very much related to its properties and mechanism of action of the plant's bioactive constituents namely the asiaticoside, asiatic acid, madecassoside and madecassic acid. As such, this review will cover the biological activity of the plant's active constituents in relation to its food and beverage applications. The plant cultivation and biotechnological approaches to improve the production of desired bioactive constituents by cultured cells will also be reviewed. In addition, the range of chemical compositions found in Centella and safety aspects are also included.